Traditional Chinese patent medicine for prophylactic treatment of migraine: a meta‐analysis of randomized, double‐blind, placebo‐controlled trials. (25th October 2014) - Xiao, Y.; Yuan, L.; Liu, Y.; Sun, X.; Cheng, J.; Wang, T.; Li, F.; Luo, R.; Zhao, X.
<x xml:space="preserve">Abstract</x> Background and purpose A large number of traditional Chinese patent medicines (TCPMs) are widely used to treat migraine in China. However, it is uncertain whether there is robust evidence on the effects of TCPMs for migraine. A meta‐analysis of randomized, double‐blind, placebo‐controlled trials was performed to evaluate the efficacy and safety of TCPMs in patients with migraine. Methods Comprehensive searches were conducted on the Medline database, Cochrane Library, the China National Knowledge Infrastructure database, the Chinese Biomedical Literature database and the Wanfang database up to December 2013. Summary estimates, including 95% confidence intervals (CIs), were calculated for frequency of migraine attacks, response rate and headache intensity. Results A total of seven trials including 582 participants with migraine met the selection criteria. TCPM was significantly more likely to reduce the frequency of migraine attacks compared with placebo (standardized mean difference −0.54; 95% CI −0.72, −0.36; P < 0.001). TCPM was associated with an improvement of response rate compared with placebo (summary relative risk 4.63, 95% CI 2.74, 7.80, P < 0.001; therapeutic gain 24.1%; number needed to treat 4.1). Headache intensity was attenuated by TCPM compared with placebo (standardized mean difference −1.33; 95% CI −1.79, −0.87; P < 0.001). The adverse events of TCPM were no different from those of placebo. Conclusion TCPMs are effective and well tolerated in the prophylactic treatment of migraine.